Development, Application, and Effectiveness of a Smart Device-based Nursing Competency Evaluation Test: A Mixed-Method Study. Issue 11 (30th November 2021) - Jang, Soyoung; Suh, Eunyoung E.
Abstract : We aimed to develop and evaluate the effectiveness of a smart device–based test to assess Korean undergraduate students' clinical nursing competency, named SBT-NURS. The 65-item SBT-NURS comprises questions that simulate clinical situations, are problem solving–oriented, use multimedia (ie, videos/photos/animations), and involve the following topics: medical-surgical nursing, fundamentals of nursing, pediatrics, maternity, management, and psychiatric. We utilized a quantitative method to analyze the effects of the SBT-NURS (ie, via a single-group, post-experimental survey design) and a qualitative method to analyze students' experiences of using the SBT-NURS (ie, via seven focus group interviews [FGIs]). Students' overall adult health nursing paper-based test scores (ie, combining their scores in group activity, presentation, attendance, and attitude toward the midterm and final tests on adult health nursing) ( r = 0.552, P < .001) and clinical practicum scores ( r = 0.268, P = .040) in the last semester showed a statistically significant positive correlation with their SBT-NURS scores. Their paper-based testing practice average scores (ie, combination between paper-based tests and clinical practicum scores) showed a similar significant correlation ( r = 0.506, P < .001). Students deemed the SBT-NURS advantageous, satisfactory, convenient, and useful. The SBT-NURS may be an effective learning and evaluation method for nursing education that help improve students' clinical competency and learning outcomes.